2012
DOI: 10.1021/ct300278x
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient and Accurate Formalism for the Treatment of Large Amplitude Intramolecular Motion

Abstract: We propose a general approach to describe large amplitude motions (LAM) with multiple degrees of freedom (DOF) in molecules or reaction intermediates, which is useful for the computation of thermochemical or kinetic data. The kinetic part of the LAM Lagrangian is derived using a Z-matrix internal coordinate representation within a new numerical procedure. This derivation is exact for a classical system, and the uncertainties on the prediction of observable quantities largely arise from uncertainties on the LAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Thus, proper treatment of internal HRs is critical to more accurately compute rates for reactions that are the focus of this work. With this in mind, we recognize more advanced methods of treating contributions to H‐transfer rates from internal rotors, but such treatments were not attempted here .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, proper treatment of internal HRs is critical to more accurately compute rates for reactions that are the focus of this work. With this in mind, we recognize more advanced methods of treating contributions to H‐transfer rates from internal rotors, but such treatments were not attempted here .…”
Section: Resultsmentioning
confidence: 99%
“…The approach discussed in this subsection bears similarity to the Bayesian calibration of force fields in molecular dynamics simulations (see, for example, Refs. [26][27][28][29][30][31][32]). The goal of this work is either to quantify the error of the molecular dynamics simulations due to the uncertainty of the molecular force fields or to obtain the force field parameters best suited for the simulations of particular properties.…”
Section: A ML Models As Simulators Of Schrödinger Equation Solutionsmentioning
confidence: 99%
“…Bayesian inference has already been used with much success in classical molecular dynamics, as exemplified by Refs. [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, we only focus on quantum control calculations along one-dimensional potentials since (1) two-or higher-dimensional intrinsic reaction paths (or their associated dipole moment surfaces, which are required for quantum control) are not readily computable and (2) much of the relevant dynamics can still be gleaned from the one-dimensional slices of the potential energy surface. To this end, prior work by us [21,30,31,32,33,34] and other researchers [26,35] have shown that an approximate path (which differs from the intrinsic/minimum path) can be parameterized with a single internal coordinate such as a bond length [21], valence bend angle [32,33,34], or dihedral angle [30,31] that can accurately describe reactions involving bond dissociation, isomerization, or internal rotation, respectively. Once a suitable reduced coordinate, x, is chosen, both V(x) and µ(x) can be readily computed in most quantum chemistry packages such as Gaussian [36], Q-Chem [37], GAMESS [38], or NWChem [39] by carrying out a relaxed potential energy scan.…”
Section: Theorymentioning
confidence: 99%